A conceptual framework for psychiatric nurses to facilitate medication compliance among adults living with depression - Jeanne du Plessis; Annie Temane; Marie Poggenpoel (AOSIS, 2024)
Background: Medication non-compliance is a significant healthcare issue that is widespread. Extensive research has identified factors that contribute to medication non-compliance in different healthcare settings. As a result, there was a need to develop a conceptual framework to facilitate medication compliance among adults living with depression. Objectives: The purpose of this study was to develop a conceptual framework for psychiatric nurses to facilitate medication compliance among adults living with depression. Method: A qualitative, exploratory, descriptive and contextual research design was utilised to investigate the experiences of adults living with depression who are non-compliant with medication. The study consisted of three phases: an empirical phase, a classification of concepts and a development phase. Following the empirical phase, a conceptual framework was developed based on the classified concepts. Results: Three sets of results were merged for the cross-validation analysis, combining findings from the systematic review, the researcher's previously conducted and published minor dissertation and the current study. Conclusion: A conceptual framework was developed to assist psychiatric nurses in effectively promoting an internal locus of control among adults living with depression. The resulting conceptual framework provides valuable insights and serves as a valuable tool for future research endeavours aimed at enhancing medication compliance among adults living with depression. Contribution: This framework serves as a valuable guide for future studies that aim to explore medication compliance among adults living with depression, specifically by focussing on the concept of internal locus of control.